Non-decisions are also decisions: power interplay between Bangladesh and India over the Brahmaputra River. Issue 4 (18th May 2020) - Vij, Sumit; Warner, Jeroen F.; Biesbroek, Robbert; Groot, Annemarie
ABSTRACT: This article shows how Bangladesh and India intentionally maintain the status quo for the Brahmaputra River at the transboundary level, using material and ideational resources. Results show that India wants to reduce its hegemonic vulnerabilities and Bangladesh aims to maintain its control over the Brahmaputra river, simultaneously building its technical and negotiation skills. We conclude that the underlying processes of maintaining the status quo can be comprehended as 'non-decision making'. The analysis presented will help policy actors to push towards a forward-looking climate change adaptation planning for the Brahmaputra River.